"La Bamba Rebelde": Chicana/o nationalism, transnational culture, and postnationalist politics. Issue 4 (December 2016) - Navarro, José
Abstract In this essay, I argue that the Chican@ music group Las Cafeteras uses theson jarocho musical genre to produce counternarratives to anti-immigrant, racist/sexist discourses in the United States and that these counternarratives simultaneously generate a broader oppositional political message to other frameworks of criminality. Las Cafeteras deploys these counternarratives by reinterpreting the song "La Bamba" as "La BambaRebelde " [emphasis added]; their call for listenersnot to believe in borders; their reappropriation of the myth of La Llorona as a method of articulating a "haunting" in the American imagination related to immigration issues; their expressed feminist Zapatista politics; and, their reliance on a cultural and political landscape in Los Angeles that allows them to re/imagine the city and the US-Mexico borderlands as a localized site of global, postnationalist politics of solidarity.